Analysis of the level of community resilience to tidal flood disaster in Banyuwangi Village, Manyar District, Gresik, East Java - Darmawan, Ridwan; Sawiji, Asri (UIN Sunan Ampel Surabaya, 2023)
Banyuwangi Village is a coastal area located in Manyar District, Gresik, East Java covering an area of 417.3982 Ha. The village has a population of 2239 people. This study aims to assess the level of community resilience affected by the tidal flood in Banyuwangi Village, Manyar District, Gresik Regency particularly in four dimensions i.e. social dimension, economic dimension, preparedness dimension, and physical dimension. The level of community resilience to tidal floods is analyzed through the Resilience Radar. Each aspect of each dimension is then analyzed to calculate the aggregate resilience index in a value range between 0.00 – 1.00. The results of the research found that the element with highest average value is the economic dimension (0.375) and the element with lowest average value is the social dimension (0.075). In aggregate, communities in Banyuwangi Village have a low level of resilience in facing flood tidal disasters.